The urban geoarchaeology of Benevento, Southern Italy: Evaluating archaeological potential. Issue 1 (24th October 2017) - Amato, Vincenzo; Ciarcia, Sabatino; Rossi, Amedeo; Santoriello, Alfonso
Abstract: The city of Benevento in the southern Apennines is located on a Pleistocene fluvial terrace almost entirely bordered by rivers. Its ancient history of human settlements dates back to the Samnitic age (fifth to third centuries B.C.). The urban landscape witnessed extensive transformation, especially during the Roman (fourth century B.C.–sixth century A.D.) and Longobard (6th–10th centuries A.D.) periods, largely as a result of destructive earthquakes and massive floods. As a consequence, large portions of the modern town were built on deep stratified archeological deposits that partially preserve the remains of previous settlements. In order to improve and expand our knowledge of the buried archaeological heritage of this town, archaeo‐stratigraphic data were integrated into a geographic information system format and database, the latter further supplemented by a detailed geomorphological study. This new dataset enabled a reassessment of the Benevento subsurface along with its archaeological assets, shedding new light on the archaeological potential of the urban area. Finally, a more reliable map of hidden cultural resources was developed, thus providing a useful tool for more suitable urban planning and project designs to help guide renovation of urban infrastructure.